Identifying functional requirements inconsistencies in multi-team projects framed into a model-based methodology - García-García, Julián Alberto; Urbieta, Mario Matías; Escalona, María José; Rossi, Gustavo Héctor; Enríquez, J. G. (2017)
REP (Requirements Engineering Process) is one of the most essential processes within the software project life cycle because it allows describing software product requirements. This specification should be as consistent as possible to enable estimating in a suitable manner the effort required to obtain the final product. REP is complex in itself, but this complexity is greatly increased in big, distributed and heterogeneous projects with multiple analyst teams and high integration among functional modules. This paper presents an approach for the systematic conciliation of functional requirements in big projects dealing with a modelbased approach. It also explains how this approach may be implemented in the context of NDT (Navigational Development Techniques) methodology and finally, it describes a preliminary evaluation of our proposal in CALIPSOneo project by analyzing the improvements obtained with our approach.
Formato de archivo PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
Journal of Web Engineering, 16(3-4), pp. 228-251.
Keywords: SOFTWARE; INGENIERÍA DE REQUERIMIENTOS